Nutritional Valuation of Biscuits from Breadfruit (Artocarpus altilis) and Wheat Flours (Triticum vulgare L.) - CÃ¡ceres, Marx IvÃ¡n GarcÃa (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The elaboration of biscuits was proposed from different percentages of breadfruit flour (Artocarpus altilis) and wheat flour (Triticum vulgare L). Materials and Methods: The samples were processed in a similar way establishing adequate times, optimal temperatures, and good practices of raw material handling. The organoleptic evaluation of the product was carried out through sensory evaluation with 10 untrained tasters, to obtain the best treatment, being this substitution: 40% breadfruit flour + 60% wheat flour, from which the bromatological and microbiological characteristics of the biscuits were determined, with permissible results within the regulations. Results: With the analyzes carried out and using the nutritional calculator of the Ecuadorian agency for regulation, control, and health surveillance â€œfor its initials in Spanish,â€ the labeling of the nutritional semaphore of the obtained product was determined by recording: â€œHighâ€ in fat content, â€œlowâ€ in sugar content, and â€œlowâ€ in salt content, which identify biscuits suitable for consumption. Conclusion: The results of the microbiological analysis quantified a mesophilic aerobic load of 298 CFU/g. The microbiological tests of molds and yeasts identified values of 18 CFU/g, being within the ranges established by the INEN standards. With respect to Escherichia coli, the results showed total absence.